2008
DOI: 10.1021/jp800378g
|View full text |Cite
|
Sign up to set email alerts
|

Orientational Order of Difluorinated Liquid Crystals: A Comparative 13C-NMR, Optical, and Dielectric Study in Nematic and Smectic B Phases

Abstract: Structural and orientational order properties of 3Cy2CyBF2 and of 5CyCy2BF2 have been investigated by means of (13)C-NMR, optical, and dielectric spectroscopy methods. In the case of NMR, order parameters have been independently obtained from the analysis of either (13)C-(19)F dipolar couplings or (13)C chemical shift anisotropies, both measured from (13)C-{(1)H} NMR static spectra. The assignment of the (13)C resonances has been carried out thanks to the comparison with solution state spectra and DFT calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…According to the Maier and Meier equations (15), the dielectric anisotropy is proportional to the order parameter divided by temperature: Á" , S(T)/T (other factors are only slightly dependent upon T). It has been shown that the S-values obtained in this way agree well with those determined by the nuclear magnetic resonance (NMR) and optical anisotropy methods (16,17). The order parameters calculated in this way are presented in Figure 9.…”
supporting
confidence: 69%
“…According to the Maier and Meier equations (15), the dielectric anisotropy is proportional to the order parameter divided by temperature: Á" , S(T)/T (other factors are only slightly dependent upon T). It has been shown that the S-values obtained in this way agree well with those determined by the nuclear magnetic resonance (NMR) and optical anisotropy methods (16,17). The order parameters calculated in this way are presented in Figure 9.…”
supporting
confidence: 69%
“…Fluorinated nematogens containing mono-fluorinated or difluorinated phenyl rings and cyclohexane in the core, structurally resembling those studied by Magnuson et al, were more recently investigated by Catalano et al [33] (3CyHeBF and 3CyCyBF2 in Table 1, with 3CyCyBF2 corresponding to 3CCP F F of 32) and Geppi et al [34] (3Cy2CyBF2 and 5CyCy2BF2 in Table 1) by 13 C NMR spectroscopy. In all cases, the use of solid state techniques and, in particular, the SPINAL-64 decoupling scheme, allowed well resolved spectra to be obtained, from which accurate 13 C-19 F splittings and anisotropic chemical shifts were measured for all the carbons of the rigid aromatic moiety, the assignment being performed on the basis of observed splittings and of the trends of signals with temperature ( Fig.…”
Section: Applicationsmentioning
confidence: 98%
“…Fluorinated nematogens containing mono‐fluorinated or di‐fluorinated phenyl rings and cyclohexane in the core, structurally resembling those studied by Magnuson et al ., were more recently investigated by Catalano et al . (3CyHeBF and 3CyCyBF2 in Table , with 3CyCyBF2 corresponding to 3CCP F F of ) and Geppi et al . (3Cy2CyBF2 and 5CyCy2BF2 in Table ) by 13 C NMR spectroscopy.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations